A Simplified procedure for total DNA isolation from coldwater fish, Schizothorax richardsonii (Gray) - Kapila, Rajeev; Mishra, D P (Indian Journal of Fisheries, 2011)
Isolation of good quality genomic DNA with desired yield is mandatory for conducting research in molecular biology. Various protocols for isolation of total DNA from fish tissues have been applied using different buffers, detergents and enzymes. Under the present investigation a simplified method for total DNA isolation from muscle tissues of coldwater fish, Schizothorax richardsonii has been developed using N-Lauroyl sarcosine (sarcosyl) as a detergent. DNA yield (45Î¼g /100 mg of fresh muscles) obtained by this method was significantly higher (P<0.05) than the methods using SDS and CTAB as detergents. Furthermore, homogenization of tissue samples was not needed which further reduced the chances of mechanical shearing of DNA.